A televisão além do controle remoto : uma análise da participação do público no telejornalismo - Barbosa, Cínthia Soares (2013)
Located in the areas of Applied Social Sciences, Communications and in the field of Studies in Journalism, this study has as its theme journalism on television, its adaptation to other means of communication and the relation with its audience. Due to this outlook of transformations, still in process, the study of telejournalism is relevant in the sense of trying to understand how these changes occur, and what may contribute to the achievement of quality journalism. In a culture of participation, the challenge of professionals who work in the field of communication is to balance the mediation of the journalist and the presence of the audience in the contents, without losing the essence of the television which already works. In the euphoria of technology possibilities, it is necessary to incorporate the ones which may really contribute. In this study, it is assumed that even with the technological transformations, television remains in its essence and potentializes its caracteristics with the digital platforms. O Jornal Hoje, from the Globo Network, the official site of the television, as well as its account on Facebook, are the objects of this research, which were investigated from the content analysis proposed by Bardin (2011). In the theoretical framework, authors, such as Maffesoli (1999), Bauman (2001), Gitelman (2006), Jenkins (2009), Cannito (2010), Brittos e Simões (2011), Lévy (1999), Scolari (2009), Castells (2003), Negroponte (1995), Gillmor (2005) e Wolton (1990), among others, were used